Uncovering data gaps in biodiversity research within Brazilian Atlantic Forest restoration - Romanelli, João P.; Kroc, Ed; Lopes Assad, Maria L.; Santos, João P. B.; Boschi, Raquel S.; Rodrigues, Ricardo R. (Restoration ecology, 2025)
Bringing together and synthesizing data from several primary studies and scales represents a powerful method for identifying patterns and gaps within forest restoration science. In this study, we employ a pioneer quantitative database‐driven review combined with spatial analysis to delineate research trends across biodiversity studies within the Brazilian Atlantic Forest (BAF). We gathered a total of 90 primary studies that met our inclusion criteria, collectively providing 822 observations (comparisons between restoration sites and reference forests) spanning restoration areas with ages ranging from 1 to 90 years old. Vascular plants and invertebrates dominated in terms of data availability, whereas soil microorganisms were the subject of limited inquiry. There is an evident disparity in the number of evidences for different forest types across regions, with mixed forest being underrepresented in relation to seasonal forest and dense forest (rainforest). On the contrary, we observed an even distribution of biodiversity outcomes across the age categories we defined for reference forests (i.e. secondary forest, secondary advanced, and old‐growth forest). Geospatial analysis revealed a concentration of research efforts within the southeastern region of the BAF. However, a significant research deficit remains for the northeast and south regions, crucial for comprehending biodiversity responses to restoration in environmental extremes. By integrating both qualitative and quantitative approaches, this framework review provides a roadmap for deepening our understanding of biodiversity responses to restoration in the BAF. Ultimately, it serves as a bridge between quantitative findings and nuanced contextual insights, guiding future research and similar studies across diverse ecosystems worldwide.